The spatial distribution of carbon dioxide in an environmental test chamber - Mahyuddin, N.; Awbi, H. (Elsevier, 2010)
The spatial distribution of CO(2) level in a classroom carried out in previous field work research has demonstrated that there is some evidence of variations in CO(2) concentration in a classroom space. Significant fluctuations in CO(2) concentration were found at different sampling points depending on the ventilation strategies and environmental conditions prevailing in individual classrooms. However, how these variations are affected by the emitting sources and the room air movement remains unknown. Hence, it was concluded that detailed investigation of the CO(2) distribution need to be performed on a smaller scale. As a result, it was decided to use an environmental chamber with various methods and rates of ventilation, for the same internal temperature and heat loads, to study the effect of ventilation strategy and air movement on the distribution of CO(2) concentration in a room. The role of human exhalation and its interaction with the plume induced by the body's convective flow and room air movement due to different ventilation strategies were studied in a chamber at the University of Reading. These phenomena are considered to be important in understanding and predicting the flow patterns in a space and how these impact on the distribution of contaminants. This paper attempts to study the CO(2) dispersion and distribution at the exhalation zone of two people sitting in a chamber as well as throughout the occupied zone of the chamber. The horizontal and vertical distributions of CO(2) were sampled at locations with a probability that CO(2) variation is considered high. Although the room size, source location, ventilation rate and location of air supply and extract devices all can have influence on the CO(2) distribution, this article gives general guidelines on the optimum positioning of CO(2) sensor in a room. (C) 2010 Elsevier Ltd. All rights reserved.